2022
DOI: 10.3390/agronomy12123093
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study for Overturning and Rollover Characteristics of a Tractor with an Implement on a Hard Surface

Abstract: The effects of the slope of the ground and the obstacle conditions on the lateral overturning/backward rollover of a tractor with an implement were analyzed through dynamic simulation. The tractor and implement’s 3D simulation model was constructed. As for simulation conditions, four heights and three shapes were set for obstacles, and eight slopes were set for the ground to be traveled by the implemented tractor. Under each condition, the critical speed at which the tractor begins to overturn and roll over wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Tractor stability against a lateral overturn is known to be determined by multiple factors [1,36]. Exterior factors such as the ground conditions (slope angle and obstacle shape and height) cannot be controlled [2,37]. Thus, interior factors can be changed to adjust tractor stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tractor stability against a lateral overturn is known to be determined by multiple factors [1,36]. Exterior factors such as the ground conditions (slope angle and obstacle shape and height) cannot be controlled [2,37]. Thus, interior factors can be changed to adjust tractor stability.…”
Section: Discussionmentioning
confidence: 99%
“…Tractors, known for their multitasking capacity, are widely used in many different farm situations [1]. In particular, tractor overturn accidents account for more than half of all tractor-related deaths [2,3]. It is no wonder that sideways overturning, or lateral rollover, accounts for the majority of overturning injuries [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Backward rollover occurred at a low-ground slope, and lateral overturning occurred at a high-ground slope. Jang et al [62] determined relative safety against lateral overturning and backward rollover when implements were attached to the same tractor and analyzed safety based on the change in the center of gravity depending on the attachment of implements. The analysis results showed that the types of lateral overturning and backward rollover changed based on a certain ground slope and that safety decreased as the ground slope and obstacle height increased.…”
Section: D Simulationmentioning
confidence: 99%
“…When attaching the plow, depth should not be excessive The implement should be lifted cautiously As the inner steering angle increases, the safety of the tractor decreases As the front wheel lift angle increases, the safety of the tractor decreases Using weight on the rear wheel located at the top of a slope increases safety [46,52,60] Ground conditions When the ground slope increases, the driving speed must be lowered The higher the obstacle, the lower the safety Maximum coefficient of static friction is the main cause of sideslip The greater the roughness of the ground, the lower the safety The presence of continuous obstacles reduces safety [31,37,46,50,54,57,58,[61][62][63] Recently, the number of studies for developing new models through theoretical analyses and comparing them with simulation results has been increasing. This trend may stem from the considerable time and cost involved in evaluating driving safety by using actual tractors or conducting dynamic experiments, coupled with the high risk of accidents owing to unexpected outcomes.…”
Section: Target Solutions Referencesmentioning
confidence: 99%
“…Compared to automobiles, tractors are often operated in difficult driving conditions, such as uneven terrain or slopes, thus having a relatively high risk of rollover accidents [1]. As per statistics, rollover accidents not only account for a large portion of agricultural machinery accidents but also cause serious injuries and driver deaths [2][3][4]. According to the U.S. Bureau of Labor Statistics [5], rollover accidents account for the highest percentage of accidents in the agricultural sector.…”
Section: Introductionmentioning
confidence: 99%